Screening the Antiangiogenic Constituents from Salvia przewalskii Maxim and Quantitative Analysis of Them - Zhu, Luping; Xiang, Cheng; Zhuang, Wenting; He, Jing; Qin, Yi; Li, Peng; Li, Baocai (Asian Journal of Chemistry, 2013)
The aim of the present study was to isolate the anti-angiogenic compounds from Salvia przewalskii Maxim rapidly and quantitative analysis of them. The activity-oriented separation method was used to isolate and the anti-angiogenic activity was evaluated by using the chicken chorioallantoic membrane (CAM) neovascularisation model and RP-HPLC was adopted to quantitative analysis. The results showed that the acetone extract from S. przewalskii was isolated into four fractions (Fr.1, Fr.2, Fr.3, Fr.4) with different polarity, among them Fr.3 could inhibit angiogenesis significantly. In order to isolate the major anti-angiogenic compounds, przewaquinone A and przewaquinone B were isolated and identified from Fr.3 and showed potential antiangiogenic activity and the contents of przewaquinone A and B in Fr.3 were 38.16 and 9.51 %, respectively. These findings suggested that przewaquinone A and B may be promising candidate for angiogenesis inhibitors, the activity combined with the contents of przewaquinone A and B in Fr.3 is the reason why did Fr.3 could inhibit angiogenesis significantly, so we can demonstrate that the relationship between pharmaceutical effect and material foundation is correlative.